Keterlibatan Masyarakat Dalam Pengelolaan Agrowisata Di Desa Tulungrejo, Kota Batu - Bella Chintya Melati; Nararya Narottama (JURNAL DESTINASI PARIWISATA, 2020)
Tulungrejo is a village located in Batu, East Java. This village surrounded by mountains and most of its people working as a farmer. The most popular agricultural product of Batu is apple and Tulungrejo is a village with the largest farm in Batu. As a village with the largest farms it should make the farmers live prosperous, but the fact shows that the farmers in Batu are not so prosperous. Since 2010 the number of apple production has also declined, many farmers choose to plant orange than apple. Some farmers of Tulungrejo Village established an Agro Tourism called Top Apel Mandiri with the aim to improve the farmer's economy. The research aim is to see how much the involvement of farmers in agro-tourism management. The method used in this research is descriptive qualitative. Data collection techniques using observation, interviews, and literature. The informant for this research are the owner of Top Apel Mandiri, the farmers in Tulungrejo, and also the vendors as the key informants. The results of this research is the community are involved in the planning and controlling process through Top Apel Mandiri, although not entirely. The the type of participation is Spontaneous Participation . At the organizing and actuating processs, the community still participates with the type of participation is Induced Participation . Keywords: agro-tourism, tourism impact, local community